Network Virtualization: Implementation Steps Towards the Future Internet - Tutschku, Kurt; Zinner, Thomas; Nakao, Akihiro; Tran-Gia, Phuoc (Electronic Communications of the EASST, 2009)
In this paper we will investigate why and how Network Virtualization (NV) can overcome the shortfalls of the current system and how it paves the way for the Future Internet. Therefore, we will first discuss some major deficiencies and achievements of today’s Internet. Afterwards, we identify three major building blocks of NV: a) the use of application-specific routing overlays, b) the safe consolidation of resources by OS virtualization on a generic infrastructure, and c) the exploitation of the network diversity for performance enhancements and for new business models, such as the provisioning of intermediate nodes or path oracles. Subsequently, we discuss an implementation scheme for network virtualization or routing overlays based on one-hop source routers (OSRs). The capabilities of the combination of NV and OSRs are demonstrated by a concurrent multipath transmission (CMP) mechanism (also known as stripping) for obtaining high throughput transmission pipes. The suggested stripping mechanism constitutes a first instance of a refinement of the concept of NV, the idea of transport system virtualization.